2019
DOI: 10.1002/ajhb.23369
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between parental consanguinity and digit ratios (2D:4D) among Turkish newborns in Sivas

Abstract: Objectives: The aim of this study was to investigate the effects of parental consanguinity on the 2D:4D digit ratio of newborn infants, whose parents were the first cousins. Methods:The study included healthy and full-term newborn infants, delivered in a hospital, at the gestational ages from 37 to 41 weeks. A total of 225 newborns and their parents were included in the study. Of these 225 newborns; 100 were inbred and 125 were outbred infants. We used a Vernier caliper to measure the length of the second and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
6
1
1
Order By: Relevance
“…Studies found in literature have shown that adult women's 2D:4D ratio is higher than adult men's 2D:4D ratio (Malas et al, 2006; Manning et al, 1998; Robinson & Manning, 2000). At the same time, 2D:4D ratio of female newborns was also found to be higher than that of male newborns (Ertuğrul & Özener, 2020; Ventura et al, 2013). However, Ventura et al (2013) did not confirm this for left hand.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Studies found in literature have shown that adult women's 2D:4D ratio is higher than adult men's 2D:4D ratio (Malas et al, 2006; Manning et al, 1998; Robinson & Manning, 2000). At the same time, 2D:4D ratio of female newborns was also found to be higher than that of male newborns (Ertuğrul & Özener, 2020; Ventura et al, 2013). However, Ventura et al (2013) did not confirm this for left hand.…”
Section: Discussionmentioning
confidence: 92%
“…Studies conducted so far have been conducted on 2D and 4D measurements of only adults or children or only on 2D and 4D measurements of newborns (Brown et al, 2002; Ertuğrul & Özener, 2020; Garn et al, 1975; Malas et al, 2006; Manning et al, 1998, 2005; Öztaşan & Kutlu, 2014; Phelps, 1952; Robinson & Manning, 2000). In fact, the number of studies on newborns is limited (Ertuğrul & Özener, 2020; Ventura et al, 2013). Almost all studies comparing mothers and newborns have been done at the hormonal level (Brown et al, 2002; Galis et al, 2010; Manning et al, 1998; Phelps, 1952; Robinson & Manning, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ïðè ýòîì, aeåíùèíû ñ áîëåå íèçêèì ïîêàçàòåëåì 2D:4D èíäåêñîì èìåëè áîëüøå øàíñîâ ðîäèòü ìàëü÷èêîâ ïî ñðàâíåíèþ ñ aeåíùèíàìè ñ áîëåå ôåìèíèííûì ñîîòíîøåíèåì. Òóðåöêèå äàííûå ïðîäåìîíñòðèðîâàëè, ÷òî èíáðèäèíã (ðîäèòåëè ÿâëÿëèñü äâîþðîäíûìè áðàòüÿìèñåñòðàìè) ìîaeåò ñóùåñòâåííî ïîâûøàòü ýìáðèîíàëüíûé ñòðåññ è ñïîñîáñòâîâàòü âíóòðèóòðîáíîé ìàñêóëèíèçàöèè [Ertugrul, Ozener, 2019].…”
Section: пальцевой индекс маскулинность/ фемининность и репродуктивнunclassified
“…However, the association between the 2D:4D ratio and prenatal testosterone (PT) and estrogen (PE) exposure was not predicted until the publication of Manning (Manning et al, 1998). It was observed that high PT exposure leads to lower digit ratios and vice versa, such that the average male has lower digit ratios as compared to the average female in many populations (Butovskaya et al, 2021; Ertuğrul & Özener, 2020; Williams et al, 2000).…”
Section: Introductionmentioning
confidence: 99%